Relação dureza/alcalinidade da água e seus efeitos sobre a qualidade da água, do solo e desempenho zootécnico de juvenis de tilápia do Nilo, Oreochromis niloticus, mantidos em condições laboratoriais - Cavalcante, Davi de Holanda (2012)
The present work aimed to determine the effects of unbalanced calcium hardness/total alkalinity (CH/TA) ratios on the water quality, soil quality and growth performance of Nile tilapia, Oreochromisniloticus, juveniles, reared in controlled conditions. Besides, it was also sought if the possible adverse effects of the unbalanced CH/TA ratios of fish growth performance could be minimized by the fish culture water’s total alkalinity (TA) increasing. The experimentswerecarried out in theLaboratório de Ciência e Tecnologia Aquicola – LCTA, ofthe Departamento de Engenharia de Pesca, Centro de Ciências Agrárias, Universidade Federal do Ceará, Fortaleza, Ceará.In this study, three complete experiments were performed. In each trial, there were six experimental groups, which were distributed according to a totally randomized design, in a 2 x 3 factorial arrangement. The first factor under scrutiny was the TA of the culture water in two levels (50 and 100 mg L-1 CaCO3 eq.).The second factor was the CH/TA ratio of the culture water in three levels (1/2, 1/1 and 5/1). In the first experiment, fish were reared in the roofed room of the laboratory, using 30 polyethylene circular 100-L tanks with no addition of bottom substrate. The second experiment was carried out in the same room used in the previous experiment, but the bottom of the tanks received a 5-cm layer of sand substrate. The third experiment was carried out in the open area of the lab in which the tank water is exposed directly to sunlight. In this last experiment, there were 36 polyethylene circular 250-L tanks with no bottom substrate. The respective stocking densities were 4, 3 and 6 fish per tank and the experiments lasted 10 (1st) and 8 (2nd and 3rd) weeks. No significant differenceswere observed between the treatments for the TA of water (50 and 100 mg L-1 CaCO3 eq.). On the other hand, there was fish growth performance impairmentcaused by the unbalanced CH/TA ratios (1/2 and 5/1) of water when compared to the control (CH/TA ratio = 1/1). The negative impact of the unbalanced CH/TA ratios on fish growth performance, either upwards (CH/TA > 1) or downwards (CH/TA < 1),was dependent on the degree that there wasbetween the absolute values of hardness and alkalinity. Small unbalance in the CH/TA ratio of culture water causedlittle growth retardation, but the higher unbalance produced considerable impairment in fish growth.